REM sleep behavior disorder and periodic leg movements during sleep in ALS. (29th March 2016) - Lo Coco, D.; Puligheddu, M.; Mattaliano, P.; Congiu, P.; Borghero, G.; Fantini, M. L.; La Bella, V.; Ferri, R.
Abstract : Objective: To assess sleep characteristics and the occurrence of abnormal muscle activity during sleep, such as REM sleep without atonia (RSWA), REM sleep behavior disorder (RBD), and periodic leg movements during sleep (PLMS), in patients with amyotrophic lateral sclerosis (ALS). Methods: A total of 41 patients with ALS and 26 healthy subjects were submitted to clinical interview and overnight video‐polysomnography. Results: A total of 22 patients with ALS (53.6%) reported poor sleep quality. Polysomnographic studies showed that patients with ALS had reduced total sleep time, increased wakefulness after sleep onset, shortened REM and slow‐wave sleep, and decreased sleep efficiency, compared to controls. Polysomnographic abnormalities were not different in patients reporting good or poor sleep and were not correlated to clinical and demographic variables. The PLMS index was significantly higher in patients with ALS than in healthy subjects, and 22 patients (53.6%) showed a PLMS index > 15/h, vs 4 (15.4%) controls ( P < 0.001). Finally, two patients with ALS (4.9%) had RBD, and two more patients presented RSWA (4.9%), whereas no controls showed abnormalities of REM sleep. Conclusion: Patients with ALS frequently present abnormalities of sleep that can be documented both at the clinical interview and at the polysomnographic evaluation, including insomnia, fragmented sleep, and increased PLMS. Moreover, abnormalities of REM sleep can be found in some of these patients.